The influence of organizational climate, leadership, and organizational culture on employee innovation capabilities - Rengganis, Claudya; Tasya, Ifa Anas; Susijawati, Noveria (Indonesian Journal of Multidisciplinary Science, 2024)
The purpose of this study is to determine the influence of independent variables, namely organizational climate variables, leadership style, organizational culture on innovation capabilities in PT. This research is a quantitative research based on the philosophy of positivism, used to examine certain populations or samples, data collection using research instruments, quantitative/artistic data analysis, with the aim of testing hypotheses that have been set. Data were collected using questionnaires developed from indicators of each variable with a Likert scale of four choices of answers from strongly agree through instrument trials and fulfillment of validity and reliability, then questionnaires were distributed to employees who were respondents. The results of hypothesis testing and regression analysis in this study show that organizational climate, leadership, and organizational culture have a significant effect on the innovation capabilities of PT, while organizational culture has a negative effect. The research analysis and discussion conclude that employees with high innovation capabilities are valuable assets, driving positive change, new solutions, and improved efficiency within the company.